2003
DOI: 10.1021/bi034582j
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Dependent Conformational Change and Thermal Stability of the Isolated PsbO Protein Detected by FTIR Spectroscopy

Abstract: The structure and function of the photosystem II PsbO extrinsic protein is under intense research, being an essential part of the biomolecular engine that carries out water oxidation and oxygen production. This paper presents a structural analysis of the isolated PsbO protein by FTIR spectroscopy, reporting detailed secondary structure quantification and changes in the secondary structure content of the protein attributed to the effect of calcium (Ca(2+)). Measurements in H(2)O and D(2)O have allowed us to see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 52 publications
5
54
1
Order By: Relevance
“…Both S-MSP and T-MSP are thermostable, and have unfolding transitions which exhibit low cooperativity which is consistent with their assignment as molten globular proteins (Heredia and De Las Rivas 2003;Loll et al 2005a;Lydakis-Simantiris et al 1999;Sonoyama et al 1996). Both can refold after heating to 90°C and can restore activity to PSII upon cooling to 25°C (LydakisSimantiris et al 1999;Sonoyama et al 1996).…”
Section: Thermostability Of Mspmentioning
confidence: 56%
See 2 more Smart Citations
“…Both S-MSP and T-MSP are thermostable, and have unfolding transitions which exhibit low cooperativity which is consistent with their assignment as molten globular proteins (Heredia and De Las Rivas 2003;Loll et al 2005a;Lydakis-Simantiris et al 1999;Sonoyama et al 1996). Both can refold after heating to 90°C and can restore activity to PSII upon cooling to 25°C (LydakisSimantiris et al 1999;Sonoyama et al 1996).…”
Section: Thermostability Of Mspmentioning
confidence: 56%
“…A multiple alignment of all known MSP sequences shows only 19 residues are completely conserved, and an additional 11 are functionally conserved, having side chains with similar properties. Most conserved residues are found in the highly conserved regions identified in references by Heredia and De Las Rivas (2003) and De Las Rivas and and shown in Fig. 3.…”
Section: Primary Structure Of Msp and Conserved Regionsmentioning
confidence: 81%
See 1 more Smart Citation
“…Stability of our free laccase and laccase immobilized on nanoparticles remained similar, but the stability of laccase immobilized on microparticles decreased. This could be caused by the changing conformation of laccase after immobilization on microparticles 35 .…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…It has been suggested that plant PsbO can bind Ca 2+ , which induces slight changes in secondary structure from a -sheet to a loop or nonordered structure, and facilitated the association of PsbO with the PSII core [Heredia & De Las Rivas, 2003, Kruk et al, 2003. However, an EPR study indicated that the functional Ca 2+ ion was not involved in the binding to PsbO [Seidler & Rutherford, 1996].…”
Section: Psbomentioning
confidence: 99%